Cloud native architecture patterns fundamentals. (O'Reilly Media, Inc., 2019)
The cloud is changing the way that enterprises, both large and small, approach how they design and build out their IT infrastructures. The many benefits of running your applications in a public, private, or hybrid cloud are, by now, well documented, and for many businesses, it's no longer a question of whether to make the move to the cloud, but when and how. But, to take the fullest advantage of the power, speed, and flexibility of the cloud, your organization needs to do more than simply drag and drop its legacy on-premises applications. You need to adopt a cloud-native architecture that makes the most effective use of cloud-based resources. In this video course, your host, Matt Stine, a 17-year veteran of the enterprise-software industry and O'Reilly author, explains what cloud-native architecture patterns are and contrasts these against more common enterprise approaches. You'll look at two of the more important concepts, DevOps and continuous delivery, and see how they combine to let your organization deliver applications in an agile and resilient fashion. You'll also explore how to best exploit the vast capabilities of cloud architectures. Learn about cloud infrastructure Examine the two complimentary approaches to delivering software via the cloud: DevOps and continuous delivery Learn about automating testing and deployments Understand how to best take advantage of the resources and capabilities that are unique to the cloud via cloud-native architecture patterns.